The association between daily total physical activity and risk of cardiovascular disease among hypertensive patients: a 10-year prospective cohort study in China - Tingyu Zhou; Jian Su; Ran Tao; Yu Qin; Jinyi Zhou; Yan Lu; Yujie Hua; Jianrong Jin; Yu Guo; Zhengming Chen; Liming Li; Ming Wu (BMC, 2021)
Abstract Background The effect of high levels of physical activity and relationship between daily total physical activity and the risk of cardiovascular disease (CVD) among hypertensive people were not clear. This study aimed to explore the optimum level of physical activity for CVD prevention. Methods Data used in the present study was derived from the sub-study of China Kadoorie Biobank study (CKB) in Jiangsu province of China. The CKB was a prospective cohort study established during 2004-2008. At baseline, 53,259 participants aged 35-74 years were recruited for the CKB Jiangsu sub-study conducted in Wuzhong district of Suzhou City. Among those 53,259 participants, the 20,179 hypertensive individuals were our study population. The outcome events were cardiovascular diseases (CVDs), while the independent variable was total daily physical activity. The Cox proportional hazard models were introduced to investigate the association between total physical activity and CVDs, reporting as hazard ratios (HR) and 95% confidence intervals (CIs). Results During a 10.1-year follow-up, 2419 CVD cases were identified. After adjustment for potential confounding factors, compared with participants at the lowest level of daily total physical activity, the hazard ratios for CVDs were 0.87 (95%CI: 0.79-0.97), 0.73 (95%CI: 0.65-0.83) and 0.75 (95%CI: 0.65-0.85) for participants within 2, 3 and 4 quartiles of physical activity. Such a negative association between total physical activity and CVDs were also observed among participants by gender and age-group, but within patients with stage 1 hypertension only. Moreover, the association of physical activity with CVDs was U-shape and the lowest HR (0.63, 95%CI: 0.54-0.74) was observed at 35.4 MET-h/d of total physical activity. Conclusions Total daily physical activity was negatively associated with CVDs among hypertensive adults in China, and this association was U-shape. It has some public health implications that community-based total physical activity intervention campaigns can be of help for CVDs prevention among hypertensive people in China.